2022
DOI: 10.3390/plants11050633
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Survey of Local Flora Used for Medicinal Purposes among Indigenous People in Five Areas in Lagos State, Nigeria

Abstract: Traditional medicine is typically the most accessible primary healthcare for a large proportion of the people in Nigeria. However, its potential remains under-explored, especially with regards to their documentation. This research investigated and documented the use of medicinal plants in the management of various health conditions/diseases among local populations in Lagos State. This study was conducted in five (5) locations of Lagos State i.e., Alimosho, Badagry, Eti-Osa, and Epe (including Ijebu and Imota).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
3
12
0
2
Order By: Relevance
“…This result may be attributed to the fact that the practice of traditional medicine or herbalism does not require a degree but is acquired by experience and learning from older generations [ 36 ]. Our result is in line with an ethnobotanical survey of local flora used for medicinal purposes conducted in Lagos, Nigeria, which reported that 79% of the participants with indigenous knowledge had only a primary education [ 39 ].…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…This result may be attributed to the fact that the practice of traditional medicine or herbalism does not require a degree but is acquired by experience and learning from older generations [ 36 ]. Our result is in line with an ethnobotanical survey of local flora used for medicinal purposes conducted in Lagos, Nigeria, which reported that 79% of the participants with indigenous knowledge had only a primary education [ 39 ].…”
Section: Resultssupporting
confidence: 88%
“…However, leaves were the most commonly used plant part for treating COVID-19 (39%) and flu (31%), while the bark (20%) was the most commonly used part for treating cough ( Figure 3 ). Several previous studies in Nigeria have also reported that leaves and bark were more utilized in the traditional treatment of different ailments than other plant parts [ 24 , 39 , 40 ]. The widespread use of leaves for herbal medicine preparation may be attributed to their relatively high abundance, accessibility, and ease of collection [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of data reveals various species that have ethnobotanical importance and used for various purposes by the indigenous people of the area. The local herbs particularly medicinal species even today assume a significant job in the financial inspire of the rustic zones and different privately created drugs are as yet being utilized as family unit solutions for different ailments [14][15][16].…”
Section: Discussionmentioning
confidence: 99%